Sling exercise and traditional warm-up have similar effects on the velocity and accuracy of throwing - Huang, J. S.; Pietrosimone, B. G.; Ingersoll, C. D.; Weltman, A. L.; Saliba, S. A. (The Journal of Strength and Conditioning Research, 2011)
Throwing is a complex motion that involves the entire body and often puts an inordinate amount of stress on the shoulder and the arm. Warm-up prepares the body for work and can enhance performance. Sling-based exercise (SE) has been theorized to activate muscles, particularly the stabilizers, in a manner beneficial for preactivity warm-up, yet this hypothesis has not been tested. Our purpose was to determine if a warm-up using SE would increase throwing velocity and accuracy compared to a traditional, thrower's 10 warm-up program. Division I baseball players (nonpitchers) (16 men, age: 19.6 ± 1.3, height: 184.2 ± 6.2 cm, mass: 76.9 ± 19.2 kg) volunteered to participate in this crossover study. All subjects underwent both a warm-up routine using a traditional method (Thrower's 10 exercises) and a warm-up routine using closed kinetic chain SE methods (RedCord) on different days separated by 72 hours. Ball velocity and accuracy measures were obtained on 10 throws after either the traditional and SE warm-up regimens. Velocity was recorded using a standard Juggs radar gun (JUGS; Tualatin, OR, USA). Accuracy was recorded using a custom accuracy target. An Analysis of covariance was performed, with the number of throws recorded before the testing was used as a covariate and p < 0.05 was set a priori. There were no statistical differences between the SE warm-up and Thrower's 10 warm-up for throwing velocity (SE: 74.7 ± 7.5 mph, Thrower's 10: 74.6 ± 7.3 mph p = 0.874) or accuracy (SE: 115.6 ± 53.7 cm, Thrower's 10: 91.8 ± 55 cm, p = 0.136). Warming up with SE produced equivalent throwing velocity and accuracy compared to the Thrower's 10 warm-up method. Thus, SE provides an alternative to traditional warm-up.